2001
DOI: 10.1046/j.1464-410x.2001.02235.x
|View full text |Cite
|
Sign up to set email alerts
|

Sheaths for urinary incontinence: a randomized crossover trial

Abstract: Objective To evaluate the full range of self-adhesive continence sheaths for men available in the UK and thus provide clinicians and consumers with a basis for product selection. Subjects and methods Fifty-eight volunteers (aged 30±89 years) tested each of six different self-adhesive sheaths available in the UK in September 1998 for 1 week each. Thirty subjects applied the sheaths themselves and 28 subjects relied on a carer to do so. During each week subjects completed a diary recording sheath changes and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…As it has been shown previously that the performance and acceptability of different urisheaths may vary [15,18,19] and that leg bag design has a considerable influence on urisheath performance [20], and considering the fact that this is the first study comparing urisheaths with APs, the observed results can apply only to the collecting device studied here (the Conveen Optima urisheath).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As it has been shown previously that the performance and acceptability of different urisheaths may vary [15,18,19] and that leg bag design has a considerable influence on urisheath performance [20], and considering the fact that this is the first study comparing urisheaths with APs, the observed results can apply only to the collecting device studied here (the Conveen Optima urisheath).…”
Section: Discussionmentioning
confidence: 93%
“…Patients are influenced by several factors when selecting a continence product, including personal preference and needs, the patients’ degree of independence, their activities and the time of day they are performed (day or night, at home or out), the nature of their UI, and the information given to them about the different methods available for managing UI [23–25]. Urisheaths are used as an alternative to an AP, and most specialists agree that their use enhances the physical and psychological well‐being of incontinent patients [18,19,26]. According to ICI recommendations, improving patient QoL must be considered first and foremost before making any decisions [1,13].…”
Section: Discussionmentioning
confidence: 99%
“…4 In addition to absorbent pads and long-term catheters there are three main devices available to men, compression devices (penile clamps), sheaths (similar to condoms), which attach to drainage bags, and pubic-pressure devices (usually a ring fitted over the penis onto which a drainage bag or system is fixed, held in place with close-fitting straps). There has been one small trial of penile compression devices 19 and several studies comparing different sheaths 20,21 and one comparing a sheath with a long-term catheter, 22 but no trials of pubic pressure devices.…”
Section: Products For Men With Moderate-heavy Urinary Incontinencementioning
confidence: 99%
“… Product performance questionnaires were based on a previously tested tool used in a study of sheath use and were piloted by seven men (five using sheath or BWU; two using clamp) to ensure questions captured all relevant aspects of product performance. These were administered at the end of each product testing (Data S1). QoL measured by the KHQ.…”
Section: Methodsmentioning
confidence: 99%